Odpowiedzi

2010-01-16T14:36:44+01:00
8a+4h=48 /:4
2a²+4ah =90 /:2

2a+h=12 ==> h=12-2a
a²+2ah=45

podstawiamy h=12-2a do drugiego równania:

a²+2a(12-2a)=45
a²+24a-4a²=45
-3a²+24a-45=0 /:(-3)
a²-8a+15=0
(a-3)(a-5)=0
a=3 lub a=5

a=3 ==> h=12-2*3=12-6=6
a=5 ==> h=12-2*5=12-10=2

Rozwiązania: a=3, h=6 lub a=5, h=2.
2010-01-16T14:49:49+01:00
8a+4h = 48 /:4
2a² + 4ah = 90

h=12-2a
2a²+4a(12-2a) = 90

2a²+48a-8a²=90
48a-6a²=90 /:6
8a - a² = 15
a (8-a) = 15
a = 15/ (8-a)
rozwiązaniem dla a będzie liczba 3 lub 5:
3 = 15/ (8-3) = 15/5 = 3
5 = 15 (8-5) = 15/3 = 5

h = 12-2a

h = 12-2*3 = 12-6 = 6
lub
h = 12-2*5 = 12-10 = 2

Rozwiązaniem są pary cyfr:
a = 3, h = 6
a = 5, h = 2